2D group-VA fluorinated antimonene: synthesis and saturable absorption. Issue 4 (10th January 2019) - Zhang, Guangju; Tang, Xian; Fu, Xing; Chen, Weicheng; Shabbir, Babar; Zhang, Han; Liu, Qiang; Gong, Mali
Abstract : 2D Group-VA fluorinated antimonene having an indirect bandgap was synthesized and the nonlinear optical response was studied. Abstract : A new derivative of antimonene named fluorinated antimonene was synthesized using the method of ionic liquid-assisted electrochemical exfoliation and synchronous fluorination. Passive Q-switched pulses were produced from a Nd:LuAG laser with fluorinated antimonene, having a pulse width of 326.7 ns and a repetition rate of 733.1 kHz demonstrating its potential application as a saturable absorber. Density functional theory calculations revealed that compared with pure antimonene with an indirect bandgap, fluorinated antimonene exhibits a direct bandgap modulated by the fluorination degree showing that fluorinated antimonene would be applied as optical devices beyond its application as a saturable absorber.